The Accuracy of the English-Indonesian of Cultural Terms in Hosseini's 'A Thousand Splendid Suns' (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
This study attempted to analyze the accuracy of cultural terms translation in A Thousand Splendid Suns novel. The objectives of the study were to describe types of cultural terms found in the novel, to identify translation strategies used, and to analyze their accuracy. This study was conducted qualitatively. Text analysis was done by comparing the original and the translated novel. The results of the study showed that there were 108 data of cultural terms that were classified into cultural categorization (ecology, material culture, social culture, organizations, customs, and ideas). The accuracy of cultural terms translation was presented in each categorization of cultural terms. The analysis of accuracy translation was supported by the accuracy scale given by three expert raters, and it later combined the strategies employed by the translator in translating cultural terms translation: translation by changing the lexicon, by translation by loan word, translation by cultural substitution, translation by paraphrasing using unrelated words, literal translation, translation by more general words, translation by less expressive word, and last one translation by omission. Four categorizations of cultural terms translation in the Indonesian translated novel were classified into accurate translation.